LARP1 integrates MYC and mTOR signaling to enable anabolic growth during tumor initiation - Pedro Fuentes; Flavia Iannizzotto; Elisa Battaglia; Chiara Balzamo; Carla Tola; Berta Forcada; Pau Bosch-i-Crespo; Francisco D. Morón-Duran; Brandon E. Frank; Carolina Martínez-Herráez; Zoi Mastora; Gabriella Manfili-Marinho; et al. (Proceedings of the National Academy of Sciences, 2026)
Tumor initiation requires the integration of oncogenic signals with environmental cues to enable anabolic growth. MYC is central to tumorigenesis, with its deregulation observed in over 60% of human cancers. Oncogenic MYC profoundly rewires transcription, enabling cells to bypass cell cycle checkpoints and reset metabolism. A cornerstone of this rewiring is the upregulation of biomass-producing pathways, particularly ribosome biogenesis. How and when MYC’s oncogenic program is translationally executed—either immediately or until a favorable metabolic context emerges—remains a central unanswered question in tumor initiation, limiting our understanding of tumor latency and early intervention. Here, we identify LARP1 as a critical effector of MYC-driven transformation, connecting MYC oncogenic activity with mTOR signaling. Mechanistically, MYC represses miR-26a/b, relieving posttranscriptional repression of LARP1 and leading to its upregulation. LARP1 associates with the translational machinery, loading it with the anabolic translatome induced by MYC in a translationally poised state. Upon permissive mTOR signaling, and dependent on the phosphorylation of LARP1 at serines 689 and 697, this program is rapidly translated, fueling the biosynthetic processes essential for tumor development. Importantly, genetic deletion of LARP1 or pharmacological mTOR inhibition completely abrogates tumor initiation in a genetically engineered colorectal organoid model of MYC-driven tumorigenesis. This underscores the physiological relevance of this two-step mechanism in which LARP1 bridges the anabolic translatome primed by MYC with its metabolic execution controlled by mTOR. By temporally uncoupling transformation from metabolic permissiveness, this mechanism defines a critical checkpoint in early tumorigenesis, revealing a potential vulnerability for intercepting MYC-driven cancer before biomass expansion.